Repere teoretice în abordarea educaţiei incluzive [Articol] - Puşca, Tatiana (CEP USM, 2012)
The changes that occurred in various spheres of human activity and developments in the further development of society have determined a new approach education, that it is essential for personality development and social integration of the individual. In this complex process must be included all children, including those who for various reasons are unable to cope withschool, their individual approach to all levels of education. Inclusive education is a priority and focus of education policy in the field.
Keywords: educaţie incluzivă